Emergence of Tetracycline Resistant Vibrio cholerae O1 Biotype El Tor Serotype Ogawa with Classical ctxB Gene from a Cholera Outbreak in Odisha, Eastern India - Jain, M. (J Pathog, 2016)
In September 2010, a cholera outbreak was reported from Odisha, Eastern India. V. cholerae isolated from the clinical samples were biochemically and serologically confirmed as serogroup O1, biotype El Tor, and serotype Ogawa. Multiplex PCR screening revealed the presence of various genes, namely, ompW, ctxB, zot, rfbO1, tcp, ace, hlyA, ompU, rtx, and toxR, in all of the isolates. The isolates were resistant to co-trimoxazole, nalidixic acid, polymyxin B, spectinomycin, streptomycin, sulfamethoxazole, tetracycline, trimethoprim, and vibriostatic agent 2,4-diamino-6,7-diisopropylpteridine (O/129). Minimum inhibitory concentration of tetracycline decreased in the presence of carbonyl cyanide m-chlorophenylhydrazone (CCCP), suggesting the involvement of efflux pumps. PCR analysis confirmed the presence of class I integrons as well as SXT elements harbouring antibiotic resistance genes in all isolates. Sequencing revealed the presence of ctxB gene of classical biotype in all the isolates. The isolates harboured an RS1-CTX prophage array with El Tor type rstR and classical ctxB on the large chromosome. The study indicated that the V. cholerae El Tor variants are evolving in the area with better antibiotic resistance and virulence potential.